Precision Grip in Congenital and Acquired Hemiparesis: Similarities in Impairments and Implications for Neurorehabilitation - Bleyenheuft, Yannick; Gordon, Andrew M. (Frontiers in Human Neuroscience, 2014)
Background: Patients with congenital and acquired hemiparesis incur long-term functional deficits, among which the loss of prehension that may impact their functional independence. Identifying, understanding and comparing the underlying mechanisms of prehension impairments represent an opportunity to better adapt neurorehabilitation Objective: The present review aims to provide a better understanding of precision grip deficits in congenital and acquired hemiparesis and to determine whether the severity and type of fine motor control impairments depend on whether or not the lesions are congenital or acquired in adulthood. Methods: Using combinations of the following key words: fingertip force, grip force, precision grip, cerebral palsy, stroke, pubmed and Scopus databases were used to search studies from 1984 to 2013. Results: Individuals with both congenital and acquired hemiparesis were able to some extent to use anticipatory motor control in precision grip tasks, even if this control was impaired in the paretic hand. In both congenital or acquired hemiparesis, the ability to plan efficient anticipatory motor control when the less-affected hand is used provides a possibility to remediate impairments in anticipatory motor control of the paretic hand. Conclusion: Surprisingly we observed very few differences between the results of studies in children with congenital hemiplegia and stroke patients. We suggest that the underlying specific strategies of neurorehabilitation developed for each one could benefit the other.